2022
DOI: 10.3390/jcm12010012
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Sedation in Patients with COVID-19-Related Acute Respiratory Distress Syndrome: An International Retrospective Study

Abstract: Background and objectives: The coronavirus disease 2019 (COVID-19) pandemic and the shortage of intravenous sedatives has led to renewed interest in inhaled sedation for patients with acute respiratory distress syndrome (ARDS). We hypothesized that inhaled sedation would be associated with improved clinical outcomes in COVID-19 ARDS patients. Methods: Retrospective international study including mechanically ventilated patients with COVID-19 ARDS who required sedation and were admitted to 10 European and US int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Despite this limitation, our study found a positive association between treatment with sevoflurane and a reduction in overall mortality in treated patients, suggesting a potential protective factor. However, further analysis is needed to identify possible confounding factors and to strengthen these outcome data ( 33 ). Increasing the sample size could provide further strength to these outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, our study found a positive association between treatment with sevoflurane and a reduction in overall mortality in treated patients, suggesting a potential protective factor. However, further analysis is needed to identify possible confounding factors and to strengthen these outcome data ( 33 ). Increasing the sample size could provide further strength to these outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous analysis [ 30 , 42 , 43 , 44 , 45 ], which found no differences between inhaled and intravenous sedation in deaths or length of ICU stay. An international retrospective study including 10 ICUs published in 2022 [ 46 ] found no association between inhaled sedation in COVID-19 patients and the number of ventilator-free days through to day 28; this suggests that the effect of treatment on mortality probably does not depend on the resulting changes in the PaO 2 /FiO 2 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, our study found a positive association between treatment with sevoflurane and a reduction in overall mortality in treated patients, suggesting a potential protective factor. However, further analysis is needed to identify possible confounding factors and to strengthen these outcome data (34). Increasing the sample size could provide further strength to these outcome data.…”
Section: Limitationsmentioning
confidence: 99%